1998
DOI: 10.1021/ma980901g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Phase Behavior of New Amphiphilic PEG-Based Triblock Copolymers as Gelling Agents for Lamellar Liquid Crystalline Phases

Abstract: We report the first evidence of the potential of new amphiphilic ABA-triblock copolymers as gelling agents for lamellar liquid crystalline L R phases. Recently, we described a new type of lamellar hydrogels which are not based on a polymer network swollen in water but are obtained by the addition of small amounts of a nonionic polymer surfactant to the fluid lamellar LR phase of the dimyristoylphosphatidyl-choline(DMPC)/pentanol/water system. In contrast with these previously reported gelling agents which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…[16,273] Hydrogels of lyotropic lamellar phases have been prepared by the addition of block molecules which act as a crosslinker between the layers. [274,275] These hydrogels show potential as new types of supramolecular bioactive materials for drug-delivery or tissue-healing applications.…”
Section: Biological Functionsmentioning
confidence: 99%
“…[16,273] Hydrogels of lyotropic lamellar phases have been prepared by the addition of block molecules which act as a crosslinker between the layers. [274,275] These hydrogels show potential as new types of supramolecular bioactive materials for drug-delivery or tissue-healing applications.…”
Section: Biological Functionsmentioning
confidence: 99%
“…[16,273] Hydrogele aus lyotropen lamellaren Phasen entstanden aus Blockmolekülen durch Zugabe eines physikalischen Vernetzers, der die Schichten miteinander verbindet. [274,275] Abbildung 26. Das Amphiphil 77 bildet eine quasiferroelektrische Struktur.…”
Section: Biologische Funktionenunclassified
“…It has been proposed that this forms a porous structure from a percolating array of ionic clusters swollen by water dispersed in a continuous polymeric matrix. 253 ' 254 Gelation is observed with as little as 0.5% added amphiphilic block copolymer. 251,252 Won et al have shown that cross-linking PS-b-PB-b-PS copolymers prior to sulfonation enables the swelling of the membrane, and hence ionic channel size, to be controlled.…”
Section: Membranesmentioning
confidence: 99%
“…25 Lipid membranes decorated with block copolymers 253. (a) Amphiphilic AB diblocks in mushroom conformations, (b) ABA triblock copolymer in bridging conformation, (c) ABA triblock copolymer in looping conformation.…”
mentioning
confidence: 99%